Desain produk aksesoris interior berbahan tempurung kelapa - Suwignjo, Daniel Putra Sutedja; Wahmuda, Faza (PRODUCTUM Jurnal Desain Produk (Pengetahuan dan Perancangan Produk), 2024)
Coconut has so various benefits that can be made for numerous products. Antoga Jaya belongs to one of food processing industries in Surabaya which uses coconuts as the raw materials for making coconut milk. This company can spend more or less 300 coconuts in which shells are not further processed and only become wastes. Considering this opportunity, the researcher used the coconut shells as the raw materials for producing goods particularly interior accessories. This applied research employed experimental technique. To get information concerning coconut shells, the researcher conducted a case study at Antoga Jaya for investigating the existing waste of coconut shells there. In addition, the researcher carried out a case study at Adjiopet Craft in Surabaya to gain information on how coconut shells could be used for making a certain product. Several phases of experiment were involved such as the processes of sorting, washing, cleaning, shaping pattern, finishing, preserving, lighting, and combining patterns as well as other materials. As a result, this research yielded the ultimate product of interior accessories such as sitting lamp, flower vase, clock, and wall-ornaments